Development of emotional labor ability scale for kindergarten teachers. - Juan Hong; Ri-Yu Pan; Yan-Jin Liu (PLoS ONE)
Kindergarten teachers' lack of emotional labor ability can lead to emotional exhaustion, burnout, identity alienation, and low job satisfaction. Systematic training is now an academic consensus. However, a suitable assessment instrument is lacking. This study aims to develop an emotional labor ability scale for kindergarten teachers and test its reliability and validity in China. First, based on the emotional labor working mechanism model, the dimensions of teachers' emotional labor ability were analyzed. Second, Behavioral Event Interview were conducted with 21 teachers to construct primary and secondary competency elements. Two rounds of expert consultation involving 5 experts revised these elements, resulting in an initial questionnaire. Finally, based on survey data from 818 teachers, various analyses (item, exploratory factor, confirmatory factor, reliability, convergence validity, and discriminant validity) were conducted. The scale has 33 items across 5 dimensions: emotional intelligence, internalizing emotional labor rules, coordination in emotional labor, reflection after emotional labor, and applying emotional labor strategies. These dimensions explain 71.757% of the variance. Confirmatory factor analysis shows good model fit (χ2/df = 2.774, RMR = 0.016, GFI = 0.918, IFI = 0.969, TLI = 0.965, CFI = 0.969, RMSEA = 0.047). Internal consistency reliability coefficients range from 0.902 to 0.953. The scale is psychometrically sound and can effectively evaluate kindergarten teachers' emotional labor ability.